Integrasi halal beauty dan ekospiritualitas dalam membentuk perilaku konsumsi islami: Pendekatan mediasi etika konsumsi - Nur Isra’ Ahmad; Farida Islamiah (Journal of Halal Industry Studies, 2026)
This study aims to analyze the influence of perceptions of halal beauty and ecospirituality on consumption behaviour, with Islamic consumption ethics as a mediating variable. The approach used is quantitative, using the Structural Equation Modelling method based on Partial Least Squares (PLS-SEM), with data from 101 Muslim female Generation Z respondents with experience or knowledge of halal beauty products. The results show that perceptions of halal beauty and ecospirituality have a positive and significant effect on Islamic consumption ethics, with ecospirituality as the dominant factor, but neither directly affects consumption behaviour. Through Islamic consumption ethics, which have been proven to be significant in mediating the relationship, it is possible to bridge ecospirituality with consumption behaviour, and fully and weakly link halal beauty perception with consumption behaviour. The implications of this study emphasize the importance of strengthening the ethical value of Islamic consumption in education, counselling, and marketing strategies for halal products, so that consumers are not only oriented towards halal labels but also towards spiritual awareness and environmental concerns.